Circular RNA circUBAP2 regulates proliferation and invasion of osteosarcoma cells through miR-641/YAP1 axis - Wu, Haojie (Cancer Cell Int, 2020)
BACKGROUND: Osteosarcoma (OS) is a common malignant bone cancer and is still a growing threat to young people. Circular RNAs (CircRNAs) are reported to be involved in the development of diverse human cancers. However, the role of circUBAP2 in OS progression is rarely reported. METHODS: Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to detect the expression levels of circUBAP2 and miR-641 in OS tissues and cells. Cell Counting Kit-8 (CCK-8) assay was employed to check cell proliferation. The ability of cell invasion was evaluated by transwell assay. The protein levels of E-cadherin, Vimentin and Yes-associated protein 1 (YAP1) were measured by western blot. The starBase was used to predict binding sites between miR-641 and circUBAP2 or YAP1 and the dual-luciferase reporter assay was performed to verify the interaction. RESULTS: The level of circUBAP2 was significantly upregulated in OS tissues and cells compared with normal tissues and cells, which was contrary to the expression of miR-641. Downregulation of circUBAP2 suppressed proliferation and invasion of OS cells and weakened the process of epithelial-mesenchymal transition (EMT). Moreover, miR-641 was a target of circUBAP2 and could bind to the 3′-untranslated region (3′UTR) of YAP1. In addition, overexpression of circUBAP2 or YAP1 reversed the inhibitory effects of miR-641 on proliferation and invasion of OS cells. Further research indicated that circUBAP2 regulated the expression of YAP1 by interacting with miR-641 in OS cells. CONCLUSION: Knockdown of circUBAP2 impeded proliferation and invasion of OS cells by downregulating the expression of YAP1 via sponging miR-641.